Development of Indonesian Soybean Industry: Comparison Between Self-Sufficiency and Import Policies - Meliany, Birka Septy; Novianti, Tanti; Tuga, Gordius Woltman (HABITAT, 2023)
The aims of this article to analyze and evaluate soybean self-sufficiency and import policies in Indonesia through policy simulations for the development of soybean self-sufficiency and imports in Indonesia. The data used in this study are annual secondary data in the form of a time series from 1995 to 2020. This research uses descriptive analysis methods, simultaneous equation models (2SLS) and alternative policy simulations. The results shows that The GDP per capita in Indonesia and the considerable 5% increase in the price of soya beans are just two of the favorable factors influencing imports. However, it also demonstrates that there are no external variables influencing Indonesia's export of soy beans. The yield of soy beans is also positively and significantly impacted by the area of the land. On the other hand, Indonesia's soya bean net export is negative and significant. There are several alternative scenarios for Indonesia's soybean policy, including the escalation of land-size (20%), GDP per capita (30%), and official exchange rate (10%). The result of the policy simulation shows that the land-size is important factor to encouraging Indonesian soybean self-sufficiency due to essential input factors.